Analysis of the Impact of Islamic Propagation Through the Kilau Ramadan Broadcast Program of KJTV on Urban Muslim Individuals in Jember - Mahfudz; Zakiyah Romadlany (Busyro: Jurnal Dakwah dan Komunikasi Islam, 2025)
This study examines the effectiveness of Islamic propagation (syiar) delivered through a local television program, “Kilau Ramadan,” broadcast by KJTV Jember, in shaping the religious understanding and attitudes of urban Muslims in Jember. While television remains a powerful audio-visual medium, the Indonesian media landscape has rapidly shifted due to digital broadcasting transition and increasing audience engagement with social media platforms. These developments encourage local broadcasters to adopt cross-platform strategies and interactive formats to sustain relevance. Using a communication and Islamic broadcasting perspective, this research explores how “Kilau Ramadan” packages religious messages, facilitates audience interaction, and positions itself within current regulatory and ethical standards of broadcasting. The study focuses on audience reception and perceived impacts, including message comprehension, motivation for religious practice, and the program’s relevance to urban daily life during Ramadan. The findings are expected to contribute to contemporary discussions on local Islamic broadcasting in the era of media convergence and to offer practical recommendations for developing contextual, ethical, and audience-centered religious programs.